2012
DOI: 10.2174/1874210601206010111
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Myoepithelial Carcinoma of High Grade Transformation: The Case Report in the Buccal Mucosa

Abstract: Epithelial-myoepithelial carcinoma was first described by Danath et al. in 1972 and is classified as a rare low-grade biphasic neoplasm of the salivary glands. This case report presents a male patient who had a lesion in the oral mucosa with a history of recurrence of the tumor. The outcome resulted in a profile consistent with an epithelial-myoepithelial carcinoma with a high degree of transformation. The case highlights the importance of histopathological evaluation of oral lesions, which occasionally may no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…The stainability and localization of S‐100 protein can be used as a supplementary tool for differential diagnosis among EMC, adenoid cystic carcinoma (ACC) and basal cell adenocarcinoma, which also possesses biphasic differentiation. The positive staining for S‐100 protein in ACC or basal cell adenocarcinoma has the tendency to localize in the inner ductal cells, while the positive staining for EMC is exclusively observed in the outer myoepithelial cells as can be seen in the present case . Calponin and glial fibrillary acidic protein (GFAP) have also been reported to be sensitive markers of myoepithelial differentiation in salivary gland tumors, but the present case showed negative for both markers as previously reported …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The stainability and localization of S‐100 protein can be used as a supplementary tool for differential diagnosis among EMC, adenoid cystic carcinoma (ACC) and basal cell adenocarcinoma, which also possesses biphasic differentiation. The positive staining for S‐100 protein in ACC or basal cell adenocarcinoma has the tendency to localize in the inner ductal cells, while the positive staining for EMC is exclusively observed in the outer myoepithelial cells as can be seen in the present case . Calponin and glial fibrillary acidic protein (GFAP) have also been reported to be sensitive markers of myoepithelial differentiation in salivary gland tumors, but the present case showed negative for both markers as previously reported …”
Section: Discussionsupporting
confidence: 86%
“…The positive staining for S-100 protein in ACC or basal cell adenocarcinoma has the tendency to localize in the inner ductal cells, while the positive staining for EMC is exclusively observed in the outer myoepithelial cells as can be seen in the present case. 16,17 Calponin and glial fibrillary acidic protein (GFAP) have also been reported to be sensitive markers of myoepithelial differentiation in salivary gland tumors, 18 but the present case showed negative for both markers as previously reported. 5 To the best of our knowledge, there are few reports on cytological features of high-grade EMC.…”
Section: Discussionsupporting
confidence: 72%
“…EMC containing a HG component has been described under various terms, including ‘‘HG carcinoma component in EMC,’’ [29] ‘‘dedifferentiated EMC,’’ [30, 33, 34, 37, 42] “EMC with/of HGT,” [35, 36, 40, 41] ‘‘aggressive EMC’’ [39] and ‘‘EMC with myoepithelial anaplasia’’ [33, 38]. Abrupt transition of the myoepithelial and/or ductal component of EMC into HG carcinoma is referred to as ‘‘dedifferentiated EMC’’ (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Seethala et al [13] stated, ''Although the name for this tumor was coined by Donath et al [1], EMC was likely recognized as early as 1956 and reported under a variety of names such as adenomyoepithelioma, clear cell adenoma, tubular solid adenoma, monomorphic clear cell tumor, glycogen-rich adenoma, glycogen-rich adenocarcinoma and clear cell carcinoma.'' EMC in minor salivary glands is distinctly rare, although some cases have been reported [14][15][16][17]. Seethala et al [13] reported the distribution of EMC by site in 58 patients as follows: parotid, 62.1 %; sinonasal, 10.3 %; palatal, 8.6 %; submandibular, 8.6 %; minor salivary gland, 6.9 %; and laryngeal, 3.4 %.…”
Section: Discussionmentioning
confidence: 99%
“…The main treatment for EMC is complete surgical resection with wide margins because of the locally invasive behavior of these tumors [15][16][17]. Adjuvant radiotherapy is also suggested in cases where the primary tumor is C4 cm or where the surgical margins are positive, but the efficacy of this technique has not been confirmed [4,6,14].…”
Section: Discussionmentioning
confidence: 99%